235 Effects of rapamycin during an acute heat stress exposure in growing pigs. (30th November 2020) - Mayorga, Edith J; Horst, Erin A; Goetz, Brady M; Rodríguez-Jiménez, Sonia; Abeyta, Megan A; Al-Qaisi, Mohmmad; Lei, Samantha; Rhoads, Robert P; Selsby, Joshua T; Baumgard, Lance H
Abstract: Objectives were to determine the effects of rapamycin on biomarkers of metabolism and inflammation during acute heat stress (HS) in growing pigs. Crossbred barrows (n=32; 63.5±0.8 BW) where blocked by BW and randomly assigned to 1 of 4 therapeutic-environmental treatments: 1) thermoneutral (TN) control (n=8; TNCtl), 2) TN and rapamycin (n=8; TNRapa), 3) HS control (n=8; HSCtl), or 4) HS and rapamycin (n=8; HSRapa). The trial consisted of 2 experimental periods (P). During P1 (10d), pigs were fed ad libitum and housed in TN conditions (21.3±0.01°C). During P2 (24h), HSCtl and HSRapa pigs were exposed to constant HS (35.5±0.1°C); while TNCtl and TNRapa remained in TN conditions. Rapamycin (0.15 mg/kg BW) was orally administered twice daily (0700 and 1800 h) during P1 and P2. HS increased rectal temperature, skin temperature, and respiration rate compared to TN counterparts (1.28°C, 8.68°C, and 87 bpm, respectively; P< 0.01). Feed intake (FI) markedly decreased in HS relative to TN treatments (64%; P< 0.01). Additionally, pigs exposed to HS lost BW (4 kg; P< 0.01), while TN pigs gained BW (0.7 kg; P< 0.01). Overall, circulating white blood cells decreased in HS compared to TN pigs (19%; P=0.01). Circulating neutrophils did not differ across treatments; however, lymphocytes, monocytes, and basophils decreased in HS relative to TN pigs (23, 33, and 38%, respectively; P≤0.07). Despite marked changes in phenotypic parameters, circulating glucose and blood urea nitrogen did not differ among treatments (P >0.10). However, insulin:FI increased in HS relative to TN treatments (P=0.04). Plasma non-esterified fatty acids (NEFA) increased in HS relative to TN treatments; although this difference was driven by increased NEFA in HSCtl compared to TN and HSRapa pigs (P< 0.01). In summary, pigs exposed to HS had altered phenotypic, metabolic, and leukocyte responses; however, rapamycin administration had little to no effect on any of the variables measured.